Increasing Economic Potential Village through the Establishment of Badan Usaha Milik Desa (BUMDES) Based on Local Wisdom - Kharis Fadlullah Hana; Lorena Dara Putri Karsono; Agep Rumanto (Bulletin of Community Engagement, 2022)
The article aimed to provide an assistance Village Leader of Jetiskapuan Village in preparing Badan Usaha Milik Desa (BUMDES). The method of this activity was carried out by providing directions for the creation of Badan Usaha Milik Desa (BUMDES) drafting team, economic potential analysis, business feasibility analysis, training for the drafting team and village deliberations for the formation of BUMDES. The results of this service are marked by an agreement on the type of business being managed, the name of the BUMDES, the capital of the bumdes, the articles of association and the by-laws of the bumdes. The line of business managed is Water Treatment and Waste Management. This service recommendation needs support and understanding between the village government and the village consultative body. PP No. 21 provides rules for BUMDES to stand alone without the involvement of the village government, the highest decision is the village meeting. This provided a lack of support from the village government at the time of BUMDES was formed. The recommendation for the results of this service is to always coordinate with the village government in order to occurs synchronization between village programs and BUMDES, besides that need to training regarding bumdes business governance for business unit development and the formation of new business units. Keywords: Economic Potential, Business Feasibility, Increasing Economic Potential